2003
DOI: 10.1002/cyto.a.10110
|View full text |Cite
|
Sign up to set email alerts
|

Double staining of Plasmodium falciparum nucleic acids with hydroethidine and thiazole orange for cell cycle stage analysis by flow cytometry

Abstract: Background: Microarray analyses of stage-specific gene expression of Plasmodium falciparum require purification of RNAs from highly synchronized cultures. To date, no reliable method to control the quality of synchronization of P. falciparum cultures is available. Methods: A double-staining method using hydroethidine and thiazole orange for nucleic acid staining was carried out to compare by flow cytometric analysis the nucleic acid labeling of synchronized P. falciparum in cultures at different time points of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Our assay demonstrated three potential markers of drug inhibition: free merozoites, ring stages, and unruptured schizonts, which are readily distinguishable by flow cytometry. In practice, detection of ring stages with non-GFP-fluorescent lines may require the application of an alternative staining method such as the combination of thiazole orange and hydroethidine (44) or Hoechst 33342 and (45). Previous studies have reported an encouraging correlation between flow cytometry and microscopy counts of drug-treated cultures in vitro (45,46) as well as application of flow cytometry to assess drug inhibition of late-stage parasite development (47).…”
Section: Discussionmentioning
confidence: 99%
“…Our assay demonstrated three potential markers of drug inhibition: free merozoites, ring stages, and unruptured schizonts, which are readily distinguishable by flow cytometry. In practice, detection of ring stages with non-GFP-fluorescent lines may require the application of an alternative staining method such as the combination of thiazole orange and hydroethidine (44) or Hoechst 33342 and (45). Previous studies have reported an encouraging correlation between flow cytometry and microscopy counts of drug-treated cultures in vitro (45,46) as well as application of flow cytometry to assess drug inhibition of late-stage parasite development (47).…”
Section: Discussionmentioning
confidence: 99%
“…To determine the growth rate of parasites, the number of infected red cells was counted over a 10-day period by flow cytometry using a fluorescence-activated cell sorter (FACS) as described previously (19,37), except that hydroethidine (at 50 g/ml) was used to stain infected RBC (18). The starting parasitemia was ϳ0.5% with a 2% hematocrit, and the cultures were diluted every 48 h after counting.…”
Section: Parasites and Transfectionmentioning
confidence: 99%
“…However, they require flow cytometers equipped with ultraviolet lasers that are not available in most laboratories. Nonspecific DNA staining agents, such as thiazole orange (7), acridine orange (8)(9)(10), ethidium bromide (11), propidium iodide (12), or hydroethidine (13)(14)(15), have also been used to stain nucleic acids from infected erythrocytes. Recently, YOYO-1, a cyanine dimer, has been added to this list (16).…”
mentioning
confidence: 99%